White Eared Kob (Kobuskobleucotis, Lichtenstein and Peters, 1854,) in Ethiopia; Migration Status, Potential Anthropogenic Threats and Conservation Directives from an Ecotourism Perspectives - Sahile Atinafa (Journal of Wildlife, 2024)
The Trans boundary protection of migratory species is a common argument for international cooperation. Ecotourism supports these activities through long-term commitment from international conservation organizations, all interest groups and various political entities. However, due to anthropogenic influences and inadequate understanding of species ecology, sustainable conservation of migratory species is often challenging. Therefore, this review article evaluates the migration status, potential anthropogenic threats, and conservation directives from the perspective of ecotourism of the white-eared kob (Kobuskobleucotis, Lichtenstein and Peters, 1854). Ethiopia. Kobus kobleucotis migrate through the Boma-Gambella border ecosystems of Ethiopia and South Sudan at certain times of the year. This migration is anonymous and requires an understanding of the overall ecology of the species. Currently, the white-eared Kob population exceeds half a million, making it the second largest migration in Africa, after the wildebeest migration in the Serengeti, Tanzania. Kobs occur in groups of five to forty depending on sex and age and are nocturnal but inactive on the hottest days. Rich grasslands and permanent water sources are the preferred habitats for the species. However, the decline in grassland potential, frequent hunting, expanding settlements, changes in land use and land cover are potential threats to the white-eared kob in Gambella National Parks. Therefore, understanding the total ecological, anthropogenic and behavioral variables that influence the movement and status of the species is the ultimate parameter for conservation activity. Furthermore, entire migration corridors require sustainable management by balancing stakeholder interests and rural community development through nature-based tourism. It is also noted that solid economic and environmental incentives through nature-based tourism require adequate protection in Gambella and the surrounding regions.
Keywords: anthropogenic threat